INSTABILITAS PARAMETRIK SISTEM POROS ROTOR DENGAN CACAT RETAK MELINTANG PARARNETRIC INSTABILITY OF CRACKED ROTOR SHUFT SYSTENS - ARI GUNAWAN, TAUFIK
In this thesis, it has been developed a numerical model using a general explicit mimerical scheme based on the Mac-Cormack\'s flux-corrected transport predictor-corrector technique in non orthogonal curvilinear grid. This numerical model has been applied to depth averaged steady lows for subcritical and supercritical free-surface flow and hydraulic jump simulations. This model is used to analyze a wide variety of hydraulic engineering problems including flows in a convergingdiverging suberitical flume, supercritical expansion at various Froude umbers, and supercritical converging chutes. For some test cases, the calculated results are compared with experimental data that has been investigated. From simulation results analysis, the comparisons with Measurements as well as with numerical solution, show that the numerical method is comparatively accurate, fast, and reliable.